Makna Hidup pada Perempuan Single Parent karena Bercerai - Adriani, Shintia; , Dra. Wiwien Dinar Prastiti, M.Si (2015)
This study discusses the meaning of life female single parent because of divorce, aims to identify and describe the meaning of life in the female single parent because of divorce. The approach in this study used a qualitative method with the number of respondents as many as seven people. Selection of informants was done by purposive sampling. Measurements were made using interviews with women who act as a single parent because of divorce. Data analysis method used in this research is data organization, coding, determine the theme, do category, and describe the category. The results showed that: 1) the meaning of life gained female single parent due to divorce is the belief that it can raise and educate a child, can be a happy family, can be useful for others, it could become a person who is more religious and has the will to become better individuals 2) the achievement of the meaning of life by women single parent is to rise from adversity and realize the factors of the meaning of life as self-understanding, act positive, intimate relationships, deepening chess value (creative values, experiential values, attitudinal values, and hopeful values ), after which the individual is able to find the wisdom behind events experienced. Keyword: the meaning of life, single parent, divorced